Poly(trimethylene carbonate) as an elastic biodegradable film for human embryonic stem cell‐derived retinal pigment epithelial cells. (4th January 2017) - Sorkio, Anni; Haimi, Suvi; Verdoold, Vincent; Juuti‐Uusitalo, Kati; Grijpma, Dirk; Skottman, Heli
Abstract: Human embryonic stem cell‐derived retinal pigment epithelial (hESC‐RPE) cell therapies show tremendous potential for the treatment of retinal degenerative diseases. A tissue engineering approach, where cells are delivered to the subretinal space on a biodegradable carrier as a sheet, shows great promise for these RPE cell therapies. The aim of the present study was to assess whether a flexible, elastic and biodegradable poly(trimethylene carbonate) (PTMC) film promotes the formation of functional hESC‐RPE and performs better than often used biodegradable poly(d, l ‐lactide) (PDLLA) film. Human ESC‐RPE maturation and functionality on PTMC films was assessed by cell proliferation assays, RPE‐specific gene and protein expression, phagocytic activity and growth factor secretion. It is demonstrated that the mechanical properties of PTMC films have close resemblance to those of the native Bruch's membrane and support the formation hESC‐RPE monolayer in serum‐free culture conditions with high degree of functionality. In contrast, use of PDLLA films did not lead to the formation of confluent monolayers of hESC‐RPE cells and had unsuitable mechanical properties for retinal application. In conclusion, the present study indicates that flexible and elastic biodegradable PTMC films show potential for retinal tissue engineering applications. Copyright © 2017 John Wiley & Sons, Ltd.